2018
DOI: 10.4172/1948-593x.1000200
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Treatment Outcome of Tuberculosis among Tuberculosis Patients in West Ethiopia

Abstract: Background: Tuberculosis is a life threatening disease caused by mycobacterium tuberculosis. In developing countries the incidence of tuberculosis has been increasing steadily since the 1990s, particularly in African countries. Several European countries have lately reported a slight increase in tuberculosis, but these are mostly related to immigrants from high-incidence countries.Objective: To assess the treatment outcomes of tuberculosis and its associated factors among tuberculosis patients on anti-tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
5
6
1
Order By: Relevance
“…The proportion of TB forms as of the analysis is 18.7%, 28.5% and 52.7% for PTB+, PTB− and EPTB respectively. This finding is comparable with the report of a related study from northwest (19.3%, 28.5% and 51.3%) and western (21.5%, 34% and 44.4%) parts of the country respectively [7, 14]. Similar findings were also reported from previous studies in Ethiopia [1517].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The proportion of TB forms as of the analysis is 18.7%, 28.5% and 52.7% for PTB+, PTB− and EPTB respectively. This finding is comparable with the report of a related study from northwest (19.3%, 28.5% and 51.3%) and western (21.5%, 34% and 44.4%) parts of the country respectively [7, 14]. Similar findings were also reported from previous studies in Ethiopia [1517].…”
Section: Discussionsupporting
confidence: 92%
“…The average death rate in this study was nearly 3%. This is low when compared to previous study reports of 10.5%, 6.3% and 7.4% in different parts of the country [7, 14, 27]. The reason might be attributed to the consorted efforts in the implementation of TB/HIV collaborative activities in the study area [6].…”
Section: Discussioncontrasting
confidence: 69%
“…4 This discrepancy might be due to the reason that the previous studies conducted among prisoners, MDR tuberculosis patients, and tuberculosis patients at referral hospitals; where complicated cases were treated causing more unsuccessful treatment outcome, whereas the current study was undergone at the general hospital; where less complicated patients were treated which increases the treatment success rate. The result of this study was almost similar to studies done in Adama city (80.8%), 27 West Ethiopia (82.5%), 3 Gonder (79%), 28 and Afar region (81.8%). 13 In this study, a successful tuberculosis treatment outcome was higher among patients treated in 2018 than those who were treated in 2015 and 2016.…”
Section: Discussionsupporting
confidence: 88%
“…11 A great issue about unsuccessful tuberculosis treatment outcome is due to drug resistance; Multiple Drug Resistance (MDR) and Extensive Drug Resistance (XDR) which was a big mankind problem causing increase burden of tuberculosis. 12 The prevalence of unsuccessful tuberculosis treatment outcome was reported in different studies; Afar (18.2%), 13 West Ethiopia (17.5%), 3 Central Africa (27.6%), 14 and India (14%). 15 The studies showed that there are different factors for poor TB treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation